Synergistic antiproliferative and anticholesterogenic effects of linalool, 1,8-cineole, and simvastatin on human cell lines - Rodenak Kladniew, Boris Emilio (2014)
Monoterpenes are naturally occurring plant hydrocarbons with multiple effects on the mevalonate pathway (MP), while statins competitively inhibit hydroxymethylglutarylcoenzyme-A reductase (HMGCR), the rate-limiting enzyme in the MP. Monoterpenes and statins proved capable of inhibiting both proliferation and cholesterogenesis. In the present study we assess the in vitro antiproliferative and anticholesterogenic effects of two monoterpenes: linalool and 1,8-cineole—either alone, in combination with each other, or combined individually with simvastatin—on liver-derived (HepG2) and extrahepatic (A549) cell lines. The three compounds alone inhibited cell proliferation in a dose-dependent fashion, while their pairwise combination produced synergistic antiproliferative effects in both cell lines. Incorporation experiments with [14C]acetate revealed that linalool and 1,8-cineole inhibited the MP, probably at different points, resulting in a reduction in cholesterogenesis and an accumulation of other MP intermediates and products. Linalool or 1,8-cineole, either together or individually with simvastatin, synergistically inhibited cholesterol synthesis. At low concentrations both monoterpenes inhibited steps specifically involved in cholesterol synthesis, whereas at higher concentrations HMGCR levels became down-regulated. Added exogenous mevalonate failed to reverse the inhibition of proliferation exerted by linalool and 1,8-cineole, suggesting that HMGCR inhibition alone is not responsible for the antiproliferative activity of those agents. This work demonstrates that monoterpenes in combination with each other, or individually in combination with simvastatin synergistically inhibits proliferation and cholesterogenesis in the human cell lines investigated, thus contributing to a clearer understanding of the action of essential-oil components, and their combination with the statins, in the targeting of specific points within a complex metabolic pathway.